Mobile Learning - Pegrum, M. author. aut Link
XVII, 257 p.
Keywords: This book explores the use of mobile devices for teaching and learning language and literacies, investigating the ways in which these technologies open up new educational possibilities. Pegrum builds up a rich picture of contemporary mobile learning and outlines of likely future developments.